Efektivitas Transformasi Kebijakan Penanggulangan Kemiskinan Kota Singkawang: Dari Bantuan Sosial ke Pemberdayaan Ekonomi - Listiyadi, Terry (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
Poverty in Singkawang City remains a strategic issue despite showing a macro downward trend to 4.53% in 2024. The main challenges lie in the extreme disparity of poverty distribution across regions, the high Open Unemployment Rate (7.92%) dominated by vocational graduates, and low access to basic infrastructure such as decent drinking water. Additionally, there is a risk of dependency on short-term social assistance which has not fully encouraged economic independence. This research aims to formulate a targeted and inclusive poverty reduction system in Singkawang City for the 2025-2029 period. The main focus includes identifying poverty characteristics at the micro level, determining priority intervention areas, and formulating integrative strategies that combine social protection with sustainable economic empowerment. This study uses a qualitative descriptive analysis approach and micro-data-based spatial analysis. Data are sourced from Statistics Indonesia (BPS) and the National Socio-Economic Single Data (DTSEN) to map poverty pockets on a by name by address basis. Composite analysis is used to establish intervention priorities in six main areas: individual, employment, health, uninhabitable housing infrastructure, water/waste infrastructure, and social. Findings show that poverty in Singkawang is dominated by structural factors, with Pasiran, Sedau, Roban, and Maya Sopa sub-districts identified as the main priority areas for intervention. The recommended reduction strategy shifts from mere social assistance (bansos) toward strengthening MSMEs, vocational training, and cross-sector data synchronization through the optimization of the TKPKD's role. The implementation of region-based policies and micro-data is projected to be able to reduce the poverty rate to a target of 3.70% by 2030 and eliminate extreme poverty sustainably.